Nexus of Service Quality, Advertising, Trust, and Customer Satisfaction: Pengaruh Kualitas Layanan, Periklanan, dan Kepercayaan terhadap Kepuasan Pelanggan pada Perusahaan Pembiayaan - Fauziah Noralia; Lilik Indayani (Academia Open, 2022)
This research investigates the influence of service quality, advertising, and trust on customer satisfaction in the context of the financial services industry. The study adopts a quantitative approach, employing multiple linear regression analysis to examine the relationships among the variables. A sample of 100 respondents, who were members of a prominent finance company, participated in the study. The findings reveal that service quality, advertising, and trust significantly impact customer satisfaction. The outcomes of this study underscore the importance of these factors in shaping customer perceptions and highlight the significance of effective service provision, advertising strategies, and trust-building initiatives for enhancing customer satisfaction in the financial services sector. These results contribute to the existing body of knowledge and hold implications for financial institutions aiming to improve customer satisfaction and loyalty. Highlights: The study examines the impact of service quality, advertising, and trust on customer satisfaction in the financing industry. Multiple linear regression analysis is used to analyze the relationships among the variables. The findings emphasize the significance of effective service provision, advertising strategies, and trust-building initiatives for enhancing customer satisfaction in financing companies. Keywords: Service Quality, Advertising, Trust, Customer Satisfaction, Financing Companies.